2014
DOI: 10.17795/ijo-3739
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Debonding Characteristics of the Conventional Metal and Self-Ligating Brackets to Enamel: An in Vitro Study

Abstract: Background: Brackets' debonding without any damage to the teeth is very important. Objectives: The aim of this study was to compare the debonding characteristics of the metal conventional and self-ligating brackets. Patients and Methods: 69 maxillary premolars were randomly assigned in 3 groups. Metal brackets of Damon, In Ovation and conventional systems were bonded to the teeth. The brackets were debonded with debonding pliers. Debonding strengths, adhesive remnant index, and enamel damage were evaluated. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The micromechanical bond which connects the adhesive agent to the acid-etched enamel causes loss of enamel at adhesiveenamel interface due to adhesive failure. 12 From the present study, the Transbond XT's mean shear bond strength was shown to be 15.33 MPa; the findings are similar to that of Pickett et al 13 and Arnold et al 14 study, which showed Transbond XT's mean shear bond strength to be 9.7 MPa. Scougall Vilchis et al 15 study, which compared the Transbond Plus with Transbond Plus and three other self-etching adhesives, showed that the Transbond XT's mean shear bond strength was highest of about 19.0 MPa compared with Transbond Plus (16.6 MPa) and other three adhesives.…”
Section: Discussionsupporting
confidence: 90%
“…The micromechanical bond which connects the adhesive agent to the acid-etched enamel causes loss of enamel at adhesiveenamel interface due to adhesive failure. 12 From the present study, the Transbond XT's mean shear bond strength was shown to be 15.33 MPa; the findings are similar to that of Pickett et al 13 and Arnold et al 14 study, which showed Transbond XT's mean shear bond strength to be 9.7 MPa. Scougall Vilchis et al 15 study, which compared the Transbond Plus with Transbond Plus and three other self-etching adhesives, showed that the Transbond XT's mean shear bond strength was highest of about 19.0 MPa compared with Transbond Plus (16.6 MPa) and other three adhesives.…”
Section: Discussionsupporting
confidence: 90%
“…10 The increase in bond strength causes the failure during the removal of the brackets; as desired, it will ensure that it is in the bracket -adhesive interface instead of in the adhesive or in the adhesive -enamel interface. 11 Many different adhesive systems are used in the literature for bonding orthodontic brackets. However, a study evaluating the bond strength of three different adhesive systems used in our study to orthodontic brackets has not been found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of in-office appointments showed that remote monitoring, such as DM, may constitute an advantage, especially for those recent orthodontic techniques that do not require such close follow-up. This is the case with self-ligating appliances (Soltani et al, 2015), where low friction brackets and light orthodontic forces allow lengthening of appointment intervals so that complete expression of the information contained in the wire is obtained (Impellizzeri et al, 2020). Other examples are orthodontic therapies carried out with aligners, that do not necessarily require a monthly interaction between patient and provider, unless an orthodontic emergency occurs.…”
Section: Effectiveness Of Dm In Reducing In-office Visitsmentioning
confidence: 99%